Profiles of and correlations among mindset, grit, and optimism in adolescents with learning disabilities: A pilot study - Tuckwiller, Beth D.; Dardick, William R.; Kutscher, Elisabeth L. (Journal of Interdisciplinary Studies in Education, 2017)
Despite increased interest in the role of “noncognitive skills” in educational contexts, there has been little exploration of their implications for youth with disabilities. We explored several constructs under the “noncognitive skills” umbrella using a survey comprised of items from the Implicit Theories of Intelligence Scale: General (Dweck, 2000) and Self-Theory (De Castella & Byrne, 2015); the Short Grit Scale (Duckworth & Quinn, 2009); and the Life Orientation Test – Revised (Scheier, Carver, & Bridges, 1994). We found notable correlations among scale scores, and preliminarily explored scale reliabilities with this population. Although sample size was small, these data are of value because they represent the first explicit exploration of these variables and their interrelationships in adolescents with learning disabilities.